Morphological Changes in Kampung Pahandut of Palangka Raya City in Response to the Cultural Shift of Riverside Communities - Priono, Yesser; Ellisa, Evawani (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2022)
Palangka Raya, the capital city of Central Kalimantan, Indonesia, had been rapidly transformed and triggered the morphological changes in both the environment and architectural order. The urban growth caused the morphological transformation, and in effect, the city of Palangka Raya continuously displayed symptoms of urban deterioration. Modernization engendered the city to lose the architectural identity of Rumah panggung (stilt houses) and suffers the environmental disorder. There has been a tendency in the city orientation to shift into an ordinary "land city". Focusing on the oldest part city in Kampung Pahandut, we conducted a field survey to map the situation on the ground. We also generated 3D mapping using the drone to obtain precisely the morphological pattern of the area. The study revealed that the condition of the waterfront environment is constantly changing. The community that lives adjacent to Kapuas River must adapt to environmental conditions by utilizing the strategy of architectural adaptations of adjustable, refillable, and movable. Although the city of Palangka Raya transformed into a land-based city and left behind the riverfront area, in the oldest part of the city at kampung Pahandut, the community still maintains the Kahayan River as the source of people’s daily lives.